2003
DOI: 10.1038/nmat953
|View full text |Cite
|
Sign up to set email alerts
|

The Mott–Hubbard insulating state and orbital degeneracy in the superconducting C603− fulleride family

Abstract: Electron correlation controls the properties of important materials such as superconducting and magnetoresistive transition metal oxides and heavy fermion systems. The role of correlation in driving metal-to-insulator transitions assumes further importance because many superconducting materials are located close to such transitions. The nature of the insulating ground state often reveals the dominant interactions in the superconductor, as shown by the importance of the properties of La2CuO4 in understanding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
61
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 29 publications
0
61
0
1
Order By: Relevance
“…The insulator Cs 3 C 60 can be turned into superconductor by pressure 13 . The superconductivity induced by pressure in Cs 3 C 60 is related to the antiferromagnetic Mott insulator 11,12 , similar to the cuprate. For the graphite superconductors with π-electron networks, C 6 Yb and C 6 Ca show superconductivity at 6.5 and 11.5 K (ref.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The insulator Cs 3 C 60 can be turned into superconductor by pressure 13 . The superconductivity induced by pressure in Cs 3 C 60 is related to the antiferromagnetic Mott insulator 11,12 , similar to the cuprate. For the graphite superconductors with π-electron networks, C 6 Yb and C 6 Ca show superconductivity at 6.5 and 11.5 K (ref.…”
mentioning
confidence: 98%
“…This behaviour is expected by the Bardeen, Cooper and Schrieffer (BCS) theory, because the expansion of lattice leads to an enhancement of the density of states on the Fermi surface. However, the body-centered-cubic fulleride Cs 3 C 60 is found to be a true Mott-Jahn-Teller insulator, and it possesses both the ingredients required by the strongly correlated theory 11,12 . The insulator Cs 3 C 60 can be turned into superconductor by pressure 13 .…”
mentioning
confidence: 99%
“…Charge transfer compounds of C 60 with alkali atoms, known as alkali fullerides, have features that resemble those of inorganic correlated systems with orbital degeneracy [3,4]. Extensive characterization in the past two decades has shown that alkali fullerides display a high degree of electron localization on individual molecules [5] and strong electron-electron interactions [6,7], and that they lie close to a metal-to-insulator transition [8,9] in which the coupling of valence electrons to intramolecular Jahn-Teller-active modes plays a crucial role [10].…”
Section: Introductionmentioning
confidence: 99%
“…In compounds of even stoichiometry (x = 2, 4) charge fluctuations are hindered both by correlation and JT effects [20][21][22], resulting in insulating and diamagnetic ground states [23][24][25], while in odd stoichiometries of cubic symmetry metallic behaviour and even phonon-mediated superconductivity (for x = 3) are observed [26][27][28]. In the latter systems a symmetry reduction involving the lifting of the LUMO degeneracy or a lattice expansion lead to an insulating state [8,9,29]. Despite the qualitative success of this description, a full quantitative understanding of metallic behaviour in fullerides is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to interesting physical and chemical properties of fullerenes, such as: superconductivity [1,2], nonlinear optics [3], ferromagnetism [4,5] and applications in solar cells [6,7], is an interesting object to study localized electronic states, magnetic properties and metal to insulator transitions [8,9]. In ordinary solids, it is difficult to observe localized charged states on a long distance, but individual fullerenes are spatially isolated, thus a pair of molecules can be used to model a system with two localized spins, similar to a diatomic molecule, but on significantly larger distance between centers.…”
mentioning
confidence: 99%